2021
DOI: 10.1186/s12913-021-06288-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between nurse managers’ work activities, nurses’ job satisfaction, patient satisfaction, and medication errors at the unit level: a correlational study

Abstract: Background Nurse managers play a critical role in enhancing nursing and patient outcomes. The work of nurse managers, who can be described as middle-managers at health care organizations, is complex and changes on a daily basis. Only a few studies have clarified how nurse managers divide their time across various work activities. This study aimed to describe the relationships between nurse managers’ work activities, nurses’ job satisfaction, patient satisfaction, and medication errors at the ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 60 publications
0
39
3
1
Order By: Relevance
“…Such support and praise can improve their job satisfaction and help maintain the participants' high satisfaction level or directly result in high-quality screening services. [27][28][29] Mazlan et al and Alhumud et al found that the score in general satisfaction dimension of their screening programmes was 3.93 and 4.28, respectively, which is lower than our findings. 30 31 Recent studies in Australia and Nepal showed that 85.2% and 38.9% of the participants were satisfied with their respective services in general satisfaction dimension, which is also lower than ours.…”
Section: Discussioncontrasting
confidence: 97%
“…Such support and praise can improve their job satisfaction and help maintain the participants' high satisfaction level or directly result in high-quality screening services. [27][28][29] Mazlan et al and Alhumud et al found that the score in general satisfaction dimension of their screening programmes was 3.93 and 4.28, respectively, which is lower than our findings. 30 31 Recent studies in Australia and Nepal showed that 85.2% and 38.9% of the participants were satisfied with their respective services in general satisfaction dimension, which is also lower than ours.…”
Section: Discussioncontrasting
confidence: 97%
“…Differences between our study findings and those obtained by other authors may not only result from the selection of research instruments and the study group size, but also from parents' expectations to be determined by the overall level of medical services in specific countries, financial aspects of the health care system, cultural factors as well as organisation and conditions of the nurse staff work, including their professional qualifications [37,38]. Multifactorial conditions of parental satisfaction with nursing care inspire further studies in this field.…”
Section: Plos Onecontrasting
confidence: 69%
“…Nurmeksela et al emphasized that managers of healthcare centers should improve the motivation and sense of security of healthcare providers by focusing on care delivery methods. They should adopt a leadership style that emphasizes safe and patient-centered care [ 39 ].…”
Section: Discussionmentioning
confidence: 99%